River damming drives population fragmentation and habitat loss of the threatened Danube streber (Zingel streber): Implications for conservation. Issue 3 (6th March 2018) - Brinker, Alexander; Chucholl, Christoph; Behrmann‐Godel, Jasminca; Matzinger, Michaela; Basen, Timo; Baer, Jan
Abstract: The Danube streber, Zingel streber, is a threatened and data‐deficient percid fish endemic to the Danube catchment. The study provides the first data on distribution, life history, and genetic structure of the species at the upstream limit of its historic distribution (south‐western Germany). A 3‐year survey effort with 143 fishing events identified several small, fragmentary populations covering only 7% of the historical range of the species. Census population sizes ( N c ) of these subpopulations were estimated from mark–recapture data at <200 individuals. Effective population sizes ( N e ), calculated from genetic data (microsatellite genotyping), were much smaller still, at <15 individuals, resulting in an N c / N e ratio of <0.25, strongly indicating that populations are seriously affected by genetic drift and inbreeding, and are thus facing a severe extinction risk. Life‐history parameters recorded during the study indicate a rapid life cycle, with both sexes probably attaining sexual maturity at the age of 1 year or older. Spawning commenced at the beginning of April and fecundity was low ( 300–400 eggs per female). Genetic analysis and mark–recapture data indicate that subpopulations of the streber live in effective isolation, separated by impassable weirs that significantly reduce genetic connectivity between subpopulations. The species is rheophilic, and limited to sites with flow velocities of 0.7 m s –1 . Hydropower infrastructure may thus also have diminished the availability of suitable habitat by reducing flow rates. Only 32% of the historical range of the Danube streber is now estimated to be morphologically suitable for the species. Furthermore, relevant parts of this range are located upstream of dams and are therefore not accessible for natural recolonization. The availability and accessibility of suitable habitats seem to be factors limiting the size of the remaining subpopulations. Conservation actions should address the restoration of degraded river habitats and increase the connectivity between isolated subpopulations of the Danube streber.